The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1139/s06-031
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of N-nitrosamines in Alberta public drinking-water distribution systems

Abstract: Since the 1974 discovery of trihalomethanes as disinfection by-products (DBPs) in drinking water, the regulatory and public health focus has been primarily directed at halogenated compounds, even though it is well established that chlorination and chloramination also produce non-halogenated DBPs. Specific halogenated DBPs that could reasonably explain the correlation of some adverse health outcomes with consumption of disinfected drinking water in a number of epidemiologic studies have yet to be identified. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(67 citation statements)
references
References 19 publications
3
61
2
1
Order By: Relevance
“…These findings are very similar to those observed when NDMA was investigated in distribution system water collected from 21 North American DWTPs (Barrett et al, 2003). However, an investigation of 20 municipal drinking water distribution systems in Alberta, Canada and 179 DWTPs in Ontario revealed NDMA concentrations of up to 100 ng/L and 66 ng/L, respectively (Charrois et al, 2007). As shown in Fig.…”
Section: Possible Occurrence and Human Risks Of Nitrosaminesmentioning
confidence: 96%
See 3 more Smart Citations
“…These findings are very similar to those observed when NDMA was investigated in distribution system water collected from 21 North American DWTPs (Barrett et al, 2003). However, an investigation of 20 municipal drinking water distribution systems in Alberta, Canada and 179 DWTPs in Ontario revealed NDMA concentrations of up to 100 ng/L and 66 ng/L, respectively (Charrois et al, 2007). As shown in Fig.…”
Section: Possible Occurrence and Human Risks Of Nitrosaminesmentioning
confidence: 96%
“…Nitrosamines as emerging DBPs have become a concern of research recently, they have been shown to be present in meats, beers, pickles, tobacco smoke and may cause adverse effects on human health (IARC, 1978;Richardson, 2009). Nitrosodimethylamine (NDMA) was initially identified as a type of DBPs in drinking water in Ontario, Canada, in 1989(Charrois et al, 2007, and as a groundwater contaminant at a northern California aerospace facility in 1998 (Najm and Trussell, 2001). In the last 10 years, the majority of studies of DBPs have focused on NDMA because it is most frequently detected in drinking water.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence of these chemicals in source water, especially NDMA, NDEA and NDBA, is significantly different from previous investigations showing very low concentrations in source waters of other countries. Most of these surveys indicated that only NDMA but no other nitrosamines was detected with lower concentrations, such as in Southeastern America (b MDL) (Uzun et al, 2015) and North America (up to 9.4 ng/L), Canada (Ontario, up to 8.0 ng/L) (Barrett et al, 2003;Charrois et al, 2007;Qian et al, 2015), and Japan (up to 4.3 ng/L) (Asami et al, 2009); besides that, Zhao et al (2008) ever reported higher concentrations of NDMA occurrence in six source waters from Canada and the United States (up to 53 ng/L). The results in our survey indicated the presence of extensive discharge sources.…”
Section: Occurrence Of Multiple Nitrosamines In Source Water and Finimentioning
confidence: 99%